Spray Gel Formulation of Goroho Banana (Musa acuminata L.) Peel Extract: Optimization and Wound Healing Activity Analysis - Madeleine Trisha Salainti; Sri Hartati Yuliani (Sanata Dharma University, 2025)
Goroho banana (Musa acuminata L.) peel extract has been traditionally used in Minahasa for wound healing. This study aimed to develop and optimize a spray gel formulation containing Goroho banana peel extract and evaluate its wound healing activity. A factorial design was employed with two factors (Carbopol 940 and HPMC) at two levels. Preliminary testing determined 3% as the optimal extract concentration through wound healing evaluation in rats. Four spray gel formulations were developed and characterized for physicochemical properties, including viscosity, pH, and drying time. Results showed Formula B (Carbopol 0.5% and HPMC 0.6%) exhibited optimal characteristics with viscosity 223.8 ± 7.6 cPs, pH 5.13 ± 0.05, and drying time 4.22 ± 0.05 minutes. The HET-CAM irritation test revealed mild irritation scores (2.5-3.8) for all formulations, with Formula B showing the lowest score (2.5). Design Expert optimization generated 100 solutions, with the optimal formula containing Carbopol 0.670% and HPMC 0.517%. The wound healing activity showed no significant differences between spray gel formulations and Bioplacenton (p0.05), indicating comparable efficacy. This study demonstrates the successful development of a safe and effective spray gel formulation of Goroho banana peel extract for wound healing applications.